Capacity and Distribution of Water Stored in the Vadose Zone of the Chinese Loess Plateau - Zhu, Y. (2020)
Water stored in the vadose (unsaturated) zone provides the majority of water required by plants and buffers water resources; thus, it is central to understanding ecological and hydrological processes in the Chinese Loess Plateau (CLP) with its thick loess deposits. We used multisource data on soil water content (SWC) and vadose zone thickness, combined with a spatial interpolation method, to quantify the vadose zone water and further deduce the water resource composition in the CLP. Vadose zone water is approximately 3.1 × 1012 m3 (±27.5%) in the CLP, 92.4% of which is stored in the deep vadose zone (>5 m and above the groundwater table). The water resources composition of the CLP comprises precipitation, river water, vadose zone water, and the saturated zone water (shallow groundwater), accounting for 2.1, 0.1, 42.1, and 55.7%, respectively. Although a large amount of water exists in the vadose zone, the SWCs in the upper (<5 m) and deep vadose zones are 47.4 and 65.3%, respectively, of the mean field capacity, both being at a low level. Our findings bridge the knowledge gaps on the deep vadose zone water and water resources composition in the CLP, providing the basis for decision‐making on balancing revegetation and water resources conservation.